Pengembangan ELKPD Berbasis Discovery Learning pada Materi Struktur dan Fungsi Jaringan Tumbuhan di Kelas XI Madrasah Aliyah - Jannah, Wildatun; Adlini, Miza Nina; Anas, Nirwana (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
The research that has been done is entitled “Development of ELKPD Based on Discovery Learning on the material structure and function of plant tissue in class XI Madrasah Aliyah”. This study aims to develop teaching materials in the from of ELKPD Based on Discovery Learning on the material structure and function of plant tissue in class XI Madrasah Aliyah which are valid, practical and effective. This study used the R&D research method with a 4D models (define, design, develop, disseminate). The test subjects in this study were class XI students of MAS Al-Ittihad Aek Nabara. The results of the media expert validation test obtained a percentage of 92% in the very feasible category and the results of the material validation test obtained a percentage of 96% in the very feasible category. The results of the practicality test assessment of the teacher’s response obtained a percentage of 89% in the very feasible category and the results of the practicality test assessment of students obtained a percentage of 99% in the very feasible category. The results of the assessment of the effectiveness test obtained an average percentage of 0,68 in the medium category. Based on the results of testing the validity, practicality and effectiveness of the product, it can be concluded that, ELKPD based on discovery learning on the material structure and function of plants tissue in class XI madrasah aliyah which is developed is feasible to be used as additional teaching material for students in the process of learning biology.